1832 : le choléra en prison, peur de l’invasion, stratégies de lutte et bilan - Céline Delétang (Criminocorpus)
The sources contained in the National Archives provide examples of different measures implemented by local and central authorities to reduce the risk of invasion of the cholera epidemic in the french prisons in 1832. The numerous exchanges between prison governors, prefets, minister, health commissions demonstrate that particular attention was paid to improving the public health in the prisons, regarded as centers of epidemic outbreak. The number of prisoners suffering and died from choleric disease seems to belie this fear, particularly in Paris where the cholera took the most toll and the prisons were filled with political prisoners.